Perancangan Web E-Commerce Pada Penjualan Jam Tangan - Ardi Nurdin; Ida Darwati (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
Internet users is increasing because the internet can be accessed anywhere and anytime. Business opportunities by utilizing the internet is increasing, especially for the sale of goods and services. Therefore, the authors raised the theme of selling goods online because it allows the introduction of the goods sold to the public with a wide range and without limitation of time, besides the benefits that can reduce the cost of promotion. Web sales of watches designed to provide booking facilities wristwatch by way of website visitors must fill out the registration form to become a member that has been provided and fill in the requested data is complete. After becoming a member then visitors can choose to your desired watches and make transactions.Keywords — E-Commerce, The Sales of Watches